الإفصاح عن الكشوف المالية وفق النظام المحاسبي المالي (SCF) في الجزائر - هلايلي اسلام (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
إن الهدف من هذه الدراسة هو توضيح وشرح وتقييم كيفية الإفصاح عن الكشوف المالية وفق النظام المحاسبي المالي في الجزائر لمستخدمي الكشوف وتبيان الإطار القانوني الذي يضمن الإفصاح عن هذه الكشوف، إن من أهم النتائج المتوصل إليها أنه وفق القوانين المعمول بها في الجزائر لعملية نشر الكشوف المالية، أنه يتول نشرها المركز الوطني للسجل التجاري في النشرة الرسمية للإعلانات القانونية للحسابات الاجتماعية في العدد الذي يلي تاريخ إيداع تلك الكشوف، وتشمل قائمة المركز المالي وجدول النتائج فقط بالنسبة للمؤسسات التجارية، دون إلزام نشر الكشوف الأخرى كما هو معمول به في المؤسسات المالية والبنوك مثل جدول سيولة الخزينة وتغير الأموال الخاصة و الملحق وهذا ما يجعل مستخدمي الكشوف لا يستطعن قراءة الكشوف بصورة سليمة، ولا يملكون صورة صادقة عن وضعية المؤسسة. The aim of this study is to clarify, explain, and evaluate how to disclose financial statements in accordance with the financial accounting system in Algeria for the users of the statements and to clarify the legal framework that guarantees the disclosure of these statements. One of the most important results reached is that it is in accordance with the laws in force in Algeria to publish financial statements, It shall be published by the National Center for the Commercial Register in the official bulletin of legal announcements of social accounts in the number that follows the date of depositing these statements, and it includes the financial center list and the results table only for commercial institutions, without the obligation to publish other statements as it is in effect In financial institutions and banks such as the treasury liquidity schedule and the change of private funds and the supplement and this is what makes the users of the statements are not able to read the statements properly, and they do not have a true picture of the status of the institution.